JC Polyomavirus (JCV) and Monoclonal Antibodies: Friends or Potential Foes? - Roberta Antonia Diotti; Akira Nakanishi; Nicola Clementi; Nicasio Mancini; Elena Criscuolo; Laura Solforosi; Massimo Clementi (Clinical and Developmental Immunology)
Progressive multifocal leukoencephalopathy (PML) is a demyelinating disease of the central nervous system (CNS), observed in immunodeficient patients and caused by JC virus ((JCV), also called JC polyomavirus (JCPyV)). After the HIV pandemic and the introduction of immunomodulatory therapy, the PML incidence significantly increased. The correlation between the use of natalizumab, a drug used in multiple sclerosis (MS), and the PML development of particular relevance. The high incidence of PML in natalizumab-treated patients has highlighted the importance of two factors: the need of PML risk stratification among natalizumab-treated patients and the need of effective therapeutic options. In this review, we discuss these two needs under the light of the major viral models of PML etiopathogenesis.